2014
DOI: 10.1039/c4cc02419b
|View full text |Cite
|
Sign up to set email alerts
|

Ionic nanoparticle networks: development and perspectives in the landscape of ionic liquid based materials

Abstract: This feature article gives an overview of the research performed on ionic nanoparticle networks (INNs). These INNs are hybrid materials consisting of inorganic nanoparticles and ionic linkers, such as imidazolium, bisimidazolium or pyridinium. The synthesis and properties of INNs, for catalysis or sensorics, are presented. At each step INN materials are compared to other hybrid materials of similar composition such as ionogels or suspensions of imidazolium modified nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 75 publications
2
14
0
1
Order By: Relevance
“…This phenomenon implies the formation of cationic networks from covalent POSS molecules, considering that the thermal stability for ionic covalent bonds is often inferior to that of covalent linkages. Similar results have been observed in such previous cationic materials as IL-like silica networks 33 and positively charged porous aromatic frameworks 30 . Figure 3b compares the FT-IR spectra of ClMePOSS and PCIF-1(M4).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This phenomenon implies the formation of cationic networks from covalent POSS molecules, considering that the thermal stability for ionic covalent bonds is often inferior to that of covalent linkages. Similar results have been observed in such previous cationic materials as IL-like silica networks 33 and positively charged porous aromatic frameworks 30 . Figure 3b compares the FT-IR spectra of ClMePOSS and PCIF-1(M4).…”
Section: Resultssupporting
confidence: 89%
“…In contrast, the ionic sites within charged networks and the resultant strong electrostatic fields are more accommodable for ionic active species and guest molecules 24 . Therefore, porous ionic solid materials are becoming hot topics in areas of porous crystals 25 , MOFs 26 27 28 29 , polymers 30 31 32 , nanoparticle networks 33 , PMOs with ionic liquids framework 34 and mesoporous ionic liquid-polyoxometalate (IL-POM) hybrids 35 36 . Such rapid emergence of ionic solid materials is thanks to their fascinating ion-exchange properties and solid-state ionic nanospaces, enabling their applications in heterogeneous catalysis 27 28 34 35 36 , gas storage and separation 26 30 32 , and ionic pollutants adsorption 29 .…”
mentioning
confidence: 99%
“…In particular, models with 5.8, 5.8 with water inside the pores, 4.8, 3.6, 2.3 and 1.7 OH nm -2 have been developed. We have shown that our models represent very well the surface of real MCM-41 silica, as evidenced by the comparison with available experimental data, and are improved compared with earlier published models [70][71][72][73][74] . The simulated IR spectra additionally confirms that our models are realistic.…”
Section: Resultssupporting
confidence: 68%
“…Moreover, these ILhybrid materials display solid-membrane like properties 19 and their properties have been investigated in detail. [20][21][22][23] The sputtering method is quite useful since the size of Pd-NPs can be easily controlled by the current discharge and metal concentration by the time of sputtering. [24][25][26] Moreover, in this method no by-products are generated and only Pd and the support are present in the catalytic material thus allowing a more accurate analysis of the interface Pd-support.…”
Section: Introductionmentioning
confidence: 99%